The effects of liquid environment on ablation efficiency and morphology of gold nanoparticles prepared by laser ablation technique - Al-Azawi, M.A.; Bidin, N.; Bououdina, C.; Alshanableh, A.; Salih, E.Y. (Trans Tech Publications, 2016)
Gold (Au) nanoparticles (NPs) were prepared by pulsed laser (Nd:YAG, 1064 nm) ablation of an individual target in deionized water (DIW), pure ethanol, and mixture of DIW and ethanol with different concentrations of ethanol. The effects of ambient liquid environment on ablation efficiency, stability, and size of Au NPs were experimentally investigated. The optical spectral characterization and morphological observations were determined by UV-Vis spectrophotometer and transmission electron microscopy, respectively. Particles are nearly spherical in shape in all liquid environments. The ablation experiment was initially performed by using DIW as the reference sample. The obtained Au NPs have an average particle size of about 18.71±7.50 nm. The comparison of the experimental results with the reference sample after a storage time of 48 h revealed that Au NPs in pure ethanol medium were not stable and exhibited much lower ablation efficiency and broader size distribution with an average particle size of 23.83±11.65 nm. Addition of ethanol with different volumes to the DIW significantly improved Au NPs properties in the mixture. The optimum ethanol concentration in the mixture was determined to be 70 vol%, which yielded the maximum ablation efficiency, rather narrow size distribution, and controllable size (12.43±8.10 nm) of Au NPs. A simple method for controlling the properties of Au NPs produced in the binary mixture of DIW-ethanol by laser ablation technique is presented.